Clinical Holistic Medicine (Mindful, Short-Term Psychodynamic Psychotherapy Complemented with Bodywork) Improves Quality of Life, Health, and Ability by Induction of Antonovsky-Salutogenesis - Søren Ventegodt; Suzette Thegler; Tove Andreasen; Flemming Struve; Lars Enevoldsen; Laila Bassaine; Margrethe Torp; Joav Merrick (The Scientific World Journal)
We had a success rate of treating low, self-assessed, global quality of life (measured by QOL1: How would you assess the quality of your life now?) with clinical holistic medicine of 56.4% (95% CI: 42.3–69.7%) and calculated from this the Number Needed to Treat (NNT) as 1.43–2.36. We found that during treatment, (in average 20 sessions of psychodynamic psychotherapy complemented with bodywork at a cost of 1600 EURO), the patients entered a state of Antonovsky-salutogenesis (holistic, existential healing), which also improved their self-assessed health and general ability one whole step up a 5-point Likert Scale. The treatment responders radically improved their self-assessed physical health (0.6 step), self-assessed mental health (1.6 step), their relation to self (1.2 step), friends (0.3 step), and partner (2.1 step on a 6-step scale), and their ability to love (1.2 step) and work (0.8 step), and to function socially (1.0 step) and sexually (0.8 step). It seems that treatment with clinical holistic medicine is the cure of choice when the patients (1) present the triad of low quality of life, poor self-assessed physical and/or mental health, and poor ability to function; and (2) are willing to suffer during the therapy by confronting and integrating old emotional problems and trauma(s) from the past. For these patients, the treatment provided lasting benefits, without the negative side effects of drugs. A lasting, positive effect might also prevent many different types of problems in the future. The therapy was “mindful” in its focus on existential and spiritual issues.